Mechanical and thermal aging behaviors of lead free solder joint with addition of porous copper interlayer / Nashrah Hani Jamadon - Nashrah Hani , Jamadon (2017)
The use of lead-based (Pb-based) solder alloy has been reduced mainly in electronics packaging due to Pb toxicity to the environment and human health. Sn-3.0Ag-0.5Cu (SAC305) Pb-free solder alloy is considered compatible combination of lead-free solder to replace conventional Pb-based solder alloy. However, it is still not as reliable as eutectic Pb-based solder alloy due to the formation of brittle intermetallic compounds (IMC), which cause a serious degradation of the joints strength. Therefore, to improve the performance characteristics of this Pb-free SAC305 solder joint, the physical soldering process was modified by incorporating a porous Cu interlayer in the soldering configuration. The SAC305 solder alloy and porous Cu interlayer was placed in a sandwich-like layer between the ends of the Cu rods to be joined. Porous Cu with 15 ppi (pore per inch, P15) and 25 ppi (P25) with approximately ϕ0.3 mm and ϕ0.1 mm pore sizes were used, respectively. A solder joint without a porous Cu interlayer was also prepared as the control sample. The soldering process was carried out at three temperatures of 267ºC, 287ºC and 307ºC, each with holding times set at 60 s, 180 s and 300 s. Tensile testing was performed to evaluate the joining strength of the solder alloy at a loading rate of 0.5 mm/min. According to the results, the tensile strength of both the control and solder containing porous Cu tended to increase with increasing soldering temperature or time. It was also found that solder containing porous Cu exhibited a strength exceeding that of the control sample by up to 10-20 MPa at each soldering temperature for each respective soldering time. The pores in the porous Cu have facilitated channels for the molten solder to penetrate into the internal porous structure before the final gripping occurred. The microstructural observation demonstrated that the growth of IMC layers at the joining interface had an apparent effect on joint reliability. Despite the relatively thin IMC layer at the SAC305/Cu substrate interface for all samples at 60 s, with higher soldering time of 180 s and 300 s, the thickness for both control and with porous Cu samples increased 1 μm for every 20°C increase of soldering temperature. In addition, a thermal aging test was performed to investigate the isothermal effect on the tensile strength and its microstructure. The isothermal aging test was done in an oven, heated to 150°C for durations of 100, 200 and 500 hours. The results indicate the significant reduction in joint strength with increasing aging time due to grain coarsening that developed from the atomic reactions in the solder alloy and porous Cu during isothermal aging. It was also observed that cracks occurred predominantly at the porous Cu/SAC305 interfaces. The present study provides a fundamental understanding of the mechanical and thermal aging characteristics of Pb-free SAC305 solder joints resulting from the addition of a porous Cu interlayer.